1986
DOI: 10.1177/000456328602300409
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Clinical Utility of a Commercially Available ‘C-terminal’ PTH Assay

Abstract: SUMMARY. The performance and clinical utility of a 'C-terminal' parathyroid hormone (PTH) radioimmunoassay (Dac-Cel, Wellcome Diagnostics) is described. Parathyroid hormone, as measured by the Dac-Cel method, is stable in whole blood samples for at least 24 h. 84% of patients with hypercalcaemia due to primary hyperparathyroidism have values above the upper limit seen in normocalcaemic subjects (0,5 ug/L), with detectable serum PTH demonstrable in the remaining 16%. In patients with hypocalcaemia due to hypopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Studies reported here and in a previous publication [5] indicate the stability of both mid-molecule and C-terminal fragments of PTH in serum.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Studies reported here and in a previous publication [5] indicate the stability of both mid-molecule and C-terminal fragments of PTH in serum.…”
Section: Discussionsupporting
confidence: 74%
“…Ingle et al [5] have previously reported data showing the stability of C-terminal PTH fragments in serum. No significant change in PTH occurred in serum left at room temperature for 24 h, even if not centrifuged and separated, and no significant change in PTH was reported after one, two or three freeze thaw cycles.…”
Section: Stability Of Pthmentioning
confidence: 99%
“…This contrasts with results previously reported in assays specific for the N-terminus,13 mid-region': 13 and C-terminus. 6 • 13. 14 However, in contrast to the results presented in the initial clinical evaluation of this assay, 4 intact PTH concentrations were suppressed in only 56% of patients in this category with the remainder having levels which fell well within the reference range.…”
Section: Serum Pth Concentrations (Fig 8)mentioning
confidence: 99%
“…'251-bovine PTH was used as the radioligand and the assay was calibrated against bovine PTH standards (Dac-Cel PTH, Wellcome Diagnostics). The assay reference range, < 200-600 ng/l, was based on manufacturers limits confirmed independently in 62 normal subjects (Ingle et al, 1986). The interassay coefficient of variation was 6%.…”
Section: Assaymentioning
confidence: 99%